The Impact of Dimensions of E-learning on the Successful Implementation and Development of Digital Pedagogy in Nepalese Higher-level Educational Institutions (OCEM Journal of Management, Technology & Social Sciences, 2023)
The dimensions of E-learning are technology, governance, awareness of E-learning, attitude toward e-learning, and e-content development, which are supported by seventeen subfactors of the vital measurements of E-learning pedagogy. The primary objective of this study was to examine the impact of the dimensions of E-learning on the successful implementation and development factors of digital pedagogy in higher education in Nepal. The quantitative research method and the survey study were applied to collect this study's data. The results indicate a significant association between social media for E-learning, the benefits of E-learning, using E-learning applications and technology, and the effective tools for teaching and the impact of E-learning dimensions for the successful implementation and development factors of digital pedagogy (p < 0.05).But the results indicate no association between the E-content and open educational resources, the effectiveness and challenges of E-Learning, E-contents and open educational resources, and the benefits of E-learning for students, E-learning practice, roles of E-learning in capacity building, effective E-learning methods, E-learning methodologies and good practices, sources of E-learning, and optimization of learner efficiency and productivity, and the impact of the dimensions of E-learning for the successful implementation and development of digital pedagogy ( p > 0.05). The implication of this study would be beneficial to policymakers, researchers, academicians, educators, and college leaders in such a way to provide first-hand information about the areas to be focused on for successful implementation and development factors on E-learning pedagogy in the Nepalese higher education sector.